Efficacy of Histick Soy in soybean nodulation in two Alfisols of Ghana - Nartey, Eric K.; Darko, Daniel A.; Sulemana, Nasirudeen; Assibey, Ernest Osei (Frontiers in Sustainable Food Systems, 2022)
Introduction Soybean is an important legume whose nitrogen-fixing ability may be exploited to improve the fertility status of soils. In Ghana, where most of the soils are poor in fertility, cultivation of soybean presents an inexpensive way for resource-poor farmers to earn appreciable income and improve the fertility of arable land at the same time. However, the yield and N-fixing response of soybean to inoculation in most soils with poor fertility in Ghana are not well-researched. Method A screen house study on the efficacy of Histick Soy (an inoculum manufactured by a German chemical company) on improving the nodulation of soybean in P-deficient soils comprising two Plinthustalfs, Ny1 and Ny2, with a history and no history, respectively, of soybean cultivation and a Kandiustalf with no history of soybean cultivation was evaluated in Ghana. Sterile riverbed sand was included as a check. Soybean seeds were inoculated with Histick Soy at three different rates, namely, zero, half, and recommended rate, and grown in a screen house to ascertain the efficacy of the inoculant in nodulating soybean. Nitrogen was applied at 0 and 10 kg/ha, K was applied at 60 kg/ha, and P was applied at 0, 30, and 60 kg/ha. These treatments were completely randomized with four replicates at a moisture content equivalent to 80% field capacity and grown till flowering. At flowering, the number of nodules per plant was counted. A parallel experiment was carried out to physiological maturity where 100-seed weight per pot was determined. Results and discussion Results obtained revealed that plants from the uninoculated seeds in the riverbed sand and the Kandiustalf did not nodulate. In the case of Ny2, the number of nodules at harvesting was statistically similar for half and full recommended application rate of the inoculant. The uninoculated Ny2 with 4.4 average nodules per pot did not increase at half recommended application rate. At the recommended rate, nodule numbers increased 2.3-fold to 10.3. The Ny1 showed no response to inoculation. Treatments, which received the application of 60 and 30 kg P2O5/ha triggered higher responses to inoculation in low and high Bradyrhizobia populations, respectively, in the Plinthustalfs.